Regulated Tristetraprolin Overexpression Dampens the Development and Pathogenesis of Experimental Autoimmune Uveitis - Xu, Biying; Tang, Jihong; Lyu, Cancan; Wandu, Wambui S.; Stumpo, Deborah J.; Mattapallil, Mary J.; Horai, Reiko; Gery, Igal; Blackshear, Perry J.; Caspi, Rachel R. (Frontiers in Immunology, 2021)
Non-infectious uveitis, a common cause of blindness in man, is often mediated by autoimmunity, a process in which cytokines play major roles. The biosynthesis and secretion of pro-inflammatory cytokines are regulated in part by tristetraprolin (TTP), an endogenous anti-inflammatory protein that acts by binding directly to specific sequence motifs in the 3’-untranslated regions of target mRNAs, promoting their turnover, and inhibiting synthesis of their encoded proteins. We recently developed a TTP-overexpressing mouse (TTPΔARE) by deleting an AU-rich element (ARE) instability motif from the TTP mRNA, resulting in increased accumulation of TTP mRNA and protein throughout the animal. Here, we show that homozygous TTPΔARE mice are resistant to the induction of experimental autoimmune uveitis (EAU) induced by interphotoreceptor retinoid-binding protein (IRBP), an established model for human autoimmune (noninfectious) uveitis. Lymphocytes from TTPΔARE mice produced lower levels of the pro-inflammatory cytokines IFN-γ, IL-17, IL-6, and TNFα than wild type (WT) mice. TTPΔARE mice also produced lower titers of antibodies against the uveitogenic protein. In contrast, TTPΔARE mice produced higher levels of the anti-inflammatory cytokine IL-10, and had higher frequencies of regulatory T-cells, which, moreover, displayed a moderately higher per-cell regulatory ability. Heterozygous mice developed EAU and associated immunological responses at levels intermediate between homozygous TTPΔARE mice and WT controls. TTPΔARE mice were able, however, to develop EAU following adoptive transfer of activated WT T-cells specific to IRBP peptide 651–670, and naïve T-cells from TTPΔARE mice could be activated by antibodies to CD3/CD28. Importantly, TTPΔARE antigen presenting cells were significantly less efficient compared to WT in priming naïve T cells, suggesting that this feature plays a major role in the dampened immune responses of the TTPΔARE mice. Our observations demonstrate that elevated systemic levels of TTP can inhibit the pathogenic processes involved in EAU, and suggest the possible use of TTP-based treatments in humans with uveitis and other autoimmune conditions.